Sudan : 2006 Article IV Consultation and Staff-Monitored Program; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Sudan. (IMF Staff Country Reports; Country Report, 2006)
Sudan's 2006 Article IV Consultation reports that growth has been robust, inflation has been kept at a single-digit level, and important reforms have been undertaken. There has been progress with financial sector reforms and trade liberalization, and the managed floating exchange rate regime has been working well. Despite an increase in oil revenues, the fiscal space of the central government will be constrained because of the transfers required by the peace agreement and decentralization.